International Sanctions and Unilateral Restrictive Measures: Problems of Definition - Kirill V. Kritskiy (Московский журнал международного права, 2016)
In this article the author examines different approaches to definition of "sanctions" and "unilateral restrictive measures". Relevant rules of international and domestic law as well as Russian and foreign doctrinal sources were analyzed for this purpose. Moreover, the author makes an effort to answer whether it is possible to terminologically identify these two phenomena with each other (as many states do to make their unilateral restrictive measures seem more legitimate).